Spring-summer mungbean for sustainable intensification: A pathway to higher yields and incomes - Sah, Uma; Rani, Rekha; Kumar, Hemant; Nath, C. P.; Chandra, Anup; Sujyanand; Maurya, G. K. Vikas; Singh, Vikrant (Indian Farming, 2025)
Mungbean (Vigna radiata L.) is a nutritionally rich pulse crop, valued for its protein, dietary fiber, vitamins, minerals, and bioactive compounds, making it a functional food for human health. Beyond its nutritional importance, mungbean serves as a short-duration crop that fits well into the cropping calendar, enabling sustainable intensification and diversification of Indian agriculture. This study reports the adoption and impact of high-yielding, disease-resistant mungbean varieties (IPM 410-3 Shikha and IPM 205-7 Virat) in spring-summer cultivation under the Farmer FIRST Programme and Model Pulse Village programmes in Kanpur Dehat and Hamirpur districts of Uttar Pradesh. Demonstrations with improved agronomic practices, including line sowing, seed treatment, and integrated insect-pest management, showed significantly higher yields (12.20–16.72 q/ha) compared to traditional practices (9.75–11.14 q/ha), resulting in additional farmer income of `1,02,354–1,06,869. The integration of short-duration mungbean into fallow or traditional cropping systems enhanced land use efficiency, crop intensification, soil health through nitrogen fixation, and profitability. These interventions highlight the potential of improved mungbean technologies to strengthen farmer livelihoods, promote sustainable intensification, and serve as a model for scaling up in similar agro-climatic zones.